The truth and beauty of chemical potentials. (2nd May 2019) - Powell, R.; Evans, K. A.; Green, E. C. R.; White, R. W.
Abstract: This essay in honour of Mike Brown addresses aspects of chemical equilibrium and equilibration in rocks, with a focus on the role that chemical potentials play. Chemical equilibrium is achieved by diffusive flattening of chemical potential gradients. The idea of equilibration volume is developed, and the way equilibration volumes may evolve along a pressure–temperature path is discussed. The effect of the environment of an equilibration volume is key to understanding the evolution of the equilibration volume with changing conditions. The likely behaviour of equilibration volumes is used to suggest why preservation of equilibrium mineral assemblages and mineral compositions from metamorphism tends to occur. This line of logic then provides the conceptual support to conventional equilibrium thermodynamic approaches to studying rocks, using, for example, thermobarometry and pseudosections.